Effect of Polylactic Acid (PLA) On Mechanical and Physical Properties of Polypropylene (PP) - Fikri, Afif (2018)
Composite materials are preferred because of many reasons such as better mechanical properties, cheaper and lighter compared to the traditional material. In this study, polypropylene was used as the matrix and polylactic acid was employed as the reinforcement. PP and PLA, show partial compatibility and the mechanical properties of the composite are inferior in contrast to the pure PP or PLA. Nonetheless, PLA in the composite had substantially better resistance to biodegradation and hydrolysis. Merging PP with PLA could be an efficient approach to create a new composite with better mechanical properties and lower price than PLA, and better dyeability, sustainability and faster degradability than PP. The objective of this study is to investigate the mechanical and physical PP/PLA composite. The composition of matrix to reinforcement weight ratio is 70/30, 50/50 and 30/70. The specimen was tested for tensile, flexural and impact properties which was compared to neat PP. PLA acts as an excellent reinforcement towards the PP/PLA composite. As a result, the tensile and flexural strength showed improvement for all the composite as the amount of PLA in the composite increases. The percentage difference of tensile strength of increase by 33.6% compared to neat PP. Moreover, the Flexural strength improved by 73.17% while flexural modulus improved by 76.59%. The reduction of impact strength was examined as all the blends of PP/PLA has lower impact strength compared to neat PP. The density of the PP/PLA composite shows a decreasing trend as the amount of PLA in the composite increases.